PENYULUHAN HIPERTENSI PADA LANSIA DI DESA PALAS KECAMATAN PALAS - Yona Desni Sagita; Siti Rohani; Yetty Dwi Fara (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Aisyah Pringsewu, 2022)
Hypertension is a major risk factor for heart disease, congestive heart failure, stroke, visual impairment and kidney disease. Diet is a person's way of eating related to eating habits every day. The factor of consuming foods high in fat, cholesterol, and excessive salt, or lack of control of eating patterns results in the high number of elderly people suffering from various diseases due to these factors. The purpose of this program is to increase the knowledge of the elderly about hypertension management. Hypertension counseling to the elderly in Palas Village, Palas District was carried out using the FGD (Focus Group Discussion) method. This activity uses an outreach method with supporting media. Hypertension counseling in the elderly uses counseling methods with interpersonal/two-way communication. After the counseling program was carried out, the results were in the form of an increase and understanding of the elderly regarding the management of hypertension.